PENGARUH BIAYA PENDIDIKAN DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN AKUNTANSI KELASXI IPS DI SMA NEGERI 2 PEKANBARU - Nisa Khairani; Sumarno Sumarno; Riadi Armas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This study aims to determine the effect of the cost of education and motivation on learning outcomes of students in class XI IPS SMAN 2 Pekanbaru. Research method used is descriptive quantitative method. Population of 107 persons and 51 samples of the students. The data collection instrument used was a questionnaire with Likert scale for the independent variable: Cost of Education (X1) and Motivation (X2), for the dependent variable using documents: Learning Outcomes(Y). Techniques of data analysis a statistical technique that is used by multiple linear regression. From the results, it can be concluded that: (1) the cost of education and motivation to learn affects the learning outcomes (2) the effect of the cost of education and student's motivation in class XI IPS SMA 2 Pekanbaru amounted to 46.5%.Key words : the cost of education, motivation, learning outcomes